Chimica generale: esercizi svolti: Raccolta di esercizi con soluzioni dettagliate per la preparazione alla prova scritta dell’esame di Chimica generale - Lamponi, Stefania (UNIverSI. Ricerca e Didattica all’Università di Siena, 2024)
The book offers a rich collection of exercises covering the fundamental topics of General Chemistry, starting from the nomenclature and classification of inorganic compounds and leading up to equilibria in aqueous solution. The exercises are organized in such a way as to provide a gradual progression in difficulty, starting with simpler problems and advancing towards those with increasing complexity. The proposed exercises also revisit the basic chemistry concepts necessary for their resolution. This approach makes the book suitable both for classroom use and individual study, providing comprehensive and in-depth training. The text is a valuable resource for anyone wishing to deepen their understanding of the subject or prepare for the Stoichiometry exam.